The usefulness of the business model disclosure for investors’ judgements in financial entities. A European study - Mechelli, Alessandro; Cimini, Riccardo; Mazzocchetti, Francesca (Revista de contabilidad, 2017)
The business model concept is a common topic investigated in different fields of research. To participate to the debate around such concept in the accounting field, the objective of this paper is showing whether and how the voluntary disclosure of the non-mandatory IASB (2010) macro-components, that we consider the key elements of a business model of financial entities, increases the value relevance of accounting amounts. Analyzing a sample of 124 European financial entities over the period 2010–2013, the paper shows that the value relevance of accounting amounts of entities that provide a wide disclosure of their business model is higher than the one of entities that provide a limited disclosure of their business model. These findings not only shed lights about the importance of disclosing information relating to the business model to improve the usefulness of accounting amounts for investors’ strategies, but also have implication for regulators and standard setters that from results could learn the opportunity to make the disclosure of IASB (2010) compulsory for all the IAS/IFRS compliant entities. El concepto de modelo de negocio es un tema de estudio frecuente en distintos campos de la investigación. Para participar en el debate en torno a dicho concepto en el ámbito de la contabilidad, el objetivo del presente artículo es mostrar si es posible y cómo la divulgación de los macrocomponentes no obligatorios de la IASB (2010), que consideramos elementos clave de un modelo de negocio para las entidades financieras, aumenta el valor de relevancia de las cantidades contables. Por medio del análisis de una muestra de 124 entidades financieras europeas en el periodo 2010-2013, el estudio muestra que la importancia al valor de las cantidades contables de las entidades que divulgan ampliamente su modelo de negocio es mayor que el de las entidades con una divulgación limitada de su modelo de negocio. Estos hallazgos no solo arrojan luz sobre la importancia de transmitir información relacionada con el modelo de negocio de cara a una mejora de la utilidad de los valores contables para las estrategias de los inversores, sino que tiene una implicación para los supervisores y organismos de normalización que podrían, a tenor de estos resultados, aprovechar la oportunidad de convertir la divulgación de la IASB (2010) en obligatoria para todas las entidades que cumplan con las normas IAS/IFRS.